Principles of forensic medicine and toxicology - Bardale, Rajesh (Jaypee Brothers Medical Pub., 2011)
Principles of Forensic Medicine & Toxicology provides a comprehensive, step by step guide to the subject. Beginning with an introduction to legal procedures, medical jurisprudence and identification, the following chapters examine forensic methods for different causes of death, such as mechanical injury, road traffic accidents, firearm injuries, thermal injuries and asphyxia. Separate chapters are dedicated to DNA profiling and forensic osteology. Almost 1000 images and illustrations, as well as a number of mnemonics, have been included to assist learning.